2013
DOI: 10.1002/lary.24464
|View full text |Cite
|
Sign up to set email alerts
|

Cricopharyngeal achalasia in children: Botulinum toxin injection as a tool for diagnosis and treatment

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…32 Therapies for such esophageal abnormalities, however, are sparse. 33,34 Despite these limitations, the GI aerodigestive evaluation objectively defined gastrointestinal tract anomalies, evaluated symptom correlation, and found histologic abnormalities. In this cohort, GI providers were often able to wean children off of their acid suppressing medications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Therapies for such esophageal abnormalities, however, are sparse. 33,34 Despite these limitations, the GI aerodigestive evaluation objectively defined gastrointestinal tract anomalies, evaluated symptom correlation, and found histologic abnormalities. In this cohort, GI providers were often able to wean children off of their acid suppressing medications.…”
Section: Resultsmentioning
confidence: 99%
“…Our center also does not routinely perform esophageal motility studies, but altered esophageal or pharyngeal motility is found in other disorders such as TEF/EA and cricopharyngeal achalasia in the aerodigestive population . Therapies for such esophageal abnormalities, however, are sparse …”
Section: Discussionmentioning
confidence: 99%
“…Cricopharyngeal achalasia (CPA) is an uncommon cause of oropharyngeal dysphagia (OPD) especially in children and it was first described in children by Utian and Thomas in 1967. 1,2 CPA is caused by failure of the upper esophageal sphincter (UES) to relax for a bolus during swallowing. 1,3 The cricopharyngeal muscle (CPM) which is the main component of UES is tonically contracted at rest and relaxes during normal swallowing to enable airway protection and propulsion of food bolus.…”
Section: Abstract: Cricopharyngeal Achalasia Dysphagia High Resolumentioning
confidence: 99%
“…1,2 CPA is caused by failure of the upper esophageal sphincter (UES) to relax for a bolus during swallowing. 1,3 The cricopharyngeal muscle (CPM) which is the main component of UES is tonically contracted at rest and relaxes during normal swallowing to enable airway protection and propulsion of food bolus. 4,5 The failure of relaxation leads to inability to swallow and increases risk for aspiration of residual food in pharynx.…”
Section: Abstract: Cricopharyngeal Achalasia Dysphagia High Resolumentioning
confidence: 99%
“…cerebral palsy, muscular dystrophy, mitochondrial encephalomyopathy, Arnold-Chiari malformation (10,11).…”
Section: Introductionmentioning
confidence: 99%